Review Literatur : Kualitas Hidup Penyandang Diabetes Mellitus Ditinjau Dari Health Locus Of Control - Ramadhani, Milenia; Induniasih, Induniasih; Sutejo, Sutejo (Publikasi Indonesia, 2022)
Health Locus of Control (HLoC) is an important indicator in self-care that plays a role in improving the quality of life for people with Diabetes Mellitus (DM). It is known that the quality of life of people with diabetes is affected by HLoC. This study uses a literature review method using the article databases PubMed, Science Direct, Proquest, Google Scholar, Cohcrane Library, Sage Publications, Researchgate, and EBSCOhost. Providing a good and correct understanding of perceptions, attitudes and behavior in people with DM can improve HLoC and their quality of life. It is proven that HloC has a positive and significant effect on the quality of life of people with DM.